A Catalytic System for the Activation of Diorganozinc Reagents. Issue 22 (23rd June 2014) - Werner, Thomas; Bauer, Matthias; Riahi, Abdol Majid; Schramm, Heiko
Abstract: We report a novel catalytic system for the activation of diorganozinc reagents. We assumed that the nucleophilic activation of diethylzinc should be efficiently performed by simple alkali metal salts. Indeed, the combination of sodium salts and 15‐crown‐5 significantly accelerates the rate of diethylzinc addition to benzaldehyde under mild conditions. The activity of the catalytic system strongly depends on the nature of the anion, decreasing in the order I –  > Br –  > Cl –  > F – . Under the optimized reaction conditions, various aryl, hetero aryl, and aliphatic aldehydes were converted with diethylzinc and the corresponding product was obtained in excellent yields. The first X‐ray absorption spectroscopy measurements on such type of reactions provide initial insights that support the proposed catalytic cycle and suggest the formation of a zincate complex. Abstract : Sodium salts in combination with crown ethers efficiently activate diorganozinc. Catalytic amounts of sodium iodide and 15‐crown‐5 promote the conversion of various aldehydes. Efforts to apply EXAFS techniques to verify the mode of activation are described.